Plasma levels of six carotenoids in nine European countries: report from the European Prospective Investigation into Cancer and Nutrition (EPIC). - Al-Delaimy, W; van Kappel, A; Ferrari, P; Slimani, N; Steghens, J; Bingham, S; Johansson, I; Wallström, P; Overvad, K; Tjønneland, A; Key, T; Welch, A; et al. (2004)
BACKGROUND: In addition to their possible direct biological effects, plasma carotenoids can be used as biochemical markers of fruit and vegetable consumption for identifying diet-disease associations in epidemiological studies. Few studies have compared levels of these carotenoids between countries in Europe. OBJECTIVE: Our aim was to assess the variability of plasma carotenoid levels within the cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC). METHODS: Plasma levels of six carotenoids--alpha-carotene, beta-carotene, beta-cryptoxanthin, lycopene, lutein and zeaxanthin--were measured cross-sectionally in 3043 study subjects from 16 regions in nine European countries. We investigated the relative influence of gender, season, age, body mass index (BMI), alcohol intake and smoking status on plasma levels of the carotenoids. RESULTS: Mean plasma level of the sum of the six carotenoids varied twofold between regions (1.35 micromol l(-1) for men in Malmö, Sweden vs. 2.79 micromol l(-1) for men in Ragusa/Naples, Italy; 1.61 micromol l(-1) for women in The Netherlands vs. 3.52 micromol l(-1) in Ragusa/Naples, Italy). Mean levels of individual carotenoids varied up to fourfold (alpha-carotene: 0.06 micromol l(-1) for men in Murcia, Spain vs. 0.25 micromol l(-1) for vegetarian men living in the UK). In multivariate regression analyses, region was the most important predictor of total plasma carotenoid level (partial R(2)=27.3%), followed by BMI (partial R(2)=5.2%), gender (partial R(2)=2.7%) and smoking status (partial R(2)=2.8%). Females had higher total carotenoid levels than males across Europe. CONCLUSIONS: Plasma levels of carotenoids vary substantially between 16 different regions in Italy, Greece, Spain, France, Germany, the UK, Sweden, Denmark and The Netherlands. Compared with region of residence, the other demographic and lifestyle factors and laboratory measurements have limited predictive value for plasma carotenoid levels in Europe.